Genetic and Functional Characterization of Toll-Like Receptor Responses in Immunocompetent Patients With CMV Mononucleosis - Frascaroli, Giada; Rossini, Giada; Maltoni, Virginia; Bartoletti, Michele; Ortolani, Patrizia; Gredmark-Russ, Sara; Gelsomino, Francesco; Moroni, Alessandra; Silenzi, Silvia; Castellani, Gastone; Sambri, Vittorio; Mastroianni, Antonio; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Background. Human cytomegalovirus (CMV) modulates both innate and adaptive immune responses. However, limited data are available on the role of receptors of innate immunity, such as toll-like receptors (TLR) in contributing to antiviral responses and inflammation. Objectives. The aim of this translational study was to characterize TLR responses in immunocompetent patients with primary and symptomatic CMV infection. Study Design. The study population consisted of 40 patients suffering of CMV mononucleosis and 124 blood donors included as controls. We evaluated the association between TLR2, 3, 4, 7 and 9 gene single nucleotide polymorphism (SNP) and susceptibility to symptomatic CMV infection in immunocompetent adults. Additionally, functional TLR-mediated cytokine responses in supernatants of short-term cultures of whole blood from patients with CMV mononucleosis and blood donors were evaluated. Results. TLR2 and TLR7/8 responses were altered in CMV infected patients as compared to healthy donors and were associated to release of higher levels of pro-inflammatory, but not anti-inflammatory mediators. The analysis on the TLRs SNP indicated no difference between patients with CMV infection and the control group. Conclusions. No variation in the TLR2,3,4,7 and 9 genes was associated to the development of symptomatic CMV infection in immunocompetent adults. Nevertheless, TLR-mediated responses in CMV-infected patients appeared to be skewed towards a pro-inflammatory profile, which may contribute to the development of inflammatory symptoms during the CMV mononucleotic syndrome.